Potential of Snakehead Fish and Sea Cucumber Extracts on Increase Anticancer Drugs Potency through Inhibition of Glutathione S-Transferase - Suhendi, Andi; Putri, Ega Annisa; Tasysaningtyas, Thalia Fiandra; Abdillah, Safira Mafaza; Aisy, Inandrohatul; Utami, Wahyu (Jurnal Kefarmasian Indonesia, 2024)
In certain conditions of cancer, isoenzymes of glutathione-S-Transferase (GST) showed increased activity. Consequently, anticancer drugs would be inactive due to increase of phase II metabolism through conjugation with glutathione. In order to increase the effectiveness of anti-cancer drugs, a GST inhibitor is required. One of the natural sources have antioxidant activity is snakehead fish. The study aims to determine GST inhibition activity of the combination of extract of snakehead fish (SF) and sea cucumber (SC). This activity was determined using rat liver and lung microsomal-cytosolic fractions obtained through the Lundgren method. GST activity was measured spectrophotometrically using a simple kinetic program at a wavelength of 345 nm with a DCNB (1.2-dichloro-4-nitrobenzene) as a substrate. The results showed an increase in the percentage of inhibition GST enzymes of the liver and lungs of rats by extracts and their combinations. The data of IC50 values showed that the smallest value for liver GST was found in SC with the value of 117.7 µg/mL and for lung GST enzymes, it was a combination of SC-SF (1:2) with a value of 45.6 µg/mL. This showed that these two samples had the greatest activity in inhibiting lung and liver GST enzymes and the potential as a complementary therapy for cancer patients.